Paddington : king of the castle - Bond, Michael; Alley, R.W. (London : HarperCollins Children's Books, 2008)
For more than five decades, stories of Paddington bear have delighted children all over the world. Nothing goes quite according to plan during Paddington's day at the beach... especially when, one by one, he joined by ten hungry seagulls. Will his lunchtime snack be safe?
Keywords: Paddington -- Juvenile literature -- Kings